The Unique N-Terminus of R-Ras Is Required for Rac Activation and Precise Regulation of Cell Migration - Holly, Stephen P. (The American Society for Cell Biology, 2005)
The Ras family GTPase, R-Ras, elicits important integrin-dependent cellular behaviors such as adhesion, spreading and migration. While oncogenic Ras GTPases and R-Ras share extensive sequence homology, R-Ras induces a distinct set of cellular behaviors. To explore the structural basis for these differences, we asked whether the unique N-terminal 26 amino acid extension of R-Ras was responsible for R-Ras–specific signaling events. Using a 32D mouse myeloid cell line, we show that full-length R-Ras activates Rac and induces Rac-dependent cell spreading. In contrast, truncated R-Ras lacking its first 26 amino acids fails to activate Rac, resulting in reduced cell spreading. Truncated R-Ras also stimulates more β3 integrin-dependent cell migration than full-length R-Ras, suggesting that the N-terminus may negatively regulate cell movement. However, neither the subcellular localization of R-Ras nor its effects on cell adhesion are affected by the presence or absence of the N-terminus. These results indicate that the N-terminus of R-Ras positively regulates specific R-Ras functions such as Rac activation and cell spreading but negatively regulates R-Ras–mediated cell migration.